Are low income children more physically active when they live in homes with bigger yards? A longitudinal analysis of the NET-Works Study. (May 2020) - Miller, Jonathan M.; Fan, Yingling; Sherwood, Nancy E.; Osypuk, Theresa; French, Simone
Abstract: This study prospectively examined the relationship of home yard-size to objectively measured physical activity over three years among a cohort of 531 low-income pre-school-aged children. An adjusted total-effect association of 12.72 additional minutes per week of moderate/vigorous physical activity (MVPA) was observed for each additional hectare of yard-size. The direct-effect association, adjusting for previous year MVPA, was not statistically significant. This study provides evidence that the private or semi-private space around the house may impact children's' physical activity. Public health and urban planning practitioners should consider these results to identify built environment solutions for improving MVPA among low-income minority children. Highlights: Larger yard size was related to more physical activity in young children. Children living in condominiums had the highest levels of physical activity. The relationship of yard-size with physical activity lessened at larger yard-sizes.